If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) = -2(6 + x) + 2x Reorder the terms: 3(4 + x) = -2(6 + x) + 2x (4 * 3 + x * 3) = -2(6 + x) + 2x (12 + 3x) = -2(6 + x) + 2x 12 + 3x = (6 * -2 + x * -2) + 2x 12 + 3x = (-12 + -2x) + 2x Combine like terms: -2x + 2x = 0 12 + 3x = -12 + 0 12 + 3x = -12 Solving 12 + 3x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = -12 + -12 3x = -12 + -12 Combine like terms: -12 + -12 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| .6666x+6=.075x | | 4=29-9y | | (x-2)-2(x-3)=2x-5 | | eg;[2]=[[3x-23]/[4]] | | -1/5w-1/3=1/4 | | -1/5w1 | | r+1.3=-0.1 | | (5a^2-10ab^3)(2a^2-5ab^3)= | | x/7-5=1;28 | | 34-v=191 | | 2x+3x+5x-4x-x=2x+10 | | 7(3)+3y=21 | | 21+3y=21 | | -8/5=-1/2u-8/3 | | 1/2x-8=-3 | | x=48/-6 | | 8k+1=2(4k-1) | | x=48-6 | | log(x-12)=2 | | 170=129-x | | (4x+5y)squared= | | 4y+5=k-7 | | m(m-g)=91 | | 10-6q=8 | | 3(3h-7)=10 | | 110/2 | | 3b+5=b+17 | | x^3-(5x^2)-125=0 | | pt+6z=y | | 2/4=4/y | | 4r+42+5r=104 | | -14=--22-×/3 |